e-Business continuity and disaster recovery plan case study: Kuwait government entities (GEs) - Al-Enezi, Khaled Abdulkareem; Alshaikhli, Imad Fakhri Taha; Al-Kandari, Abdul Rahman; Al-Mutairi, Hessa Mutlaq (2013)
cyber-attack is spyware devices through pernicious files to change logic data and computers code. That leads to distributive results that expose data for risk. Organizations have to define the risks and appraise their impact. Disaster recovery plan and business continuity plan are developed to deter interruptions to business. From analyzing the survey of case study of business continuity(BC) and disaster recovery(DR) plan in Kuwait government entities (GES), that a large ratio of Kuwait GES have business continuity(BC) & disaster recovery (DR)plan. The proportions of the attack on their systems are very weak.